The Invisible Discrimination Before Our Eyes: A Bioethical Analysis. (23rd December 2016) - Minerva, Francesca
Abstract: The goal of this article is to introduce a philosophical analysis of a widely neglected condition which affects between 3% and 18% of the population. People affected by this condition (which will be revealed later in the article) experience a lower level of wellbeing than the average population and are discriminated against in both their professional and their personal life. I will argue that this form of discrimination should be taken more seriously in philosophical debate and that social, legal and medical measures ought to be taken in order to improve the quality of life of people affected by this condition.